ANALISIS MANAJEMEN AGING PROCESS PROBLEM DI POSBINDU WILAYAH PUSKESMAS BARENG MALANG DENGAN PENDEKATAN MODEL PRECEED PROCEDE - Monika Luhung (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2020)
Background: The aging process is one of the life cycles that is characterized by a progressive decline in all physical and psychological functions. Growing old is inevitable and greatly affects the health of the elderly and the environment. Method: Precede-proceed is used in solving the elderly problem, it is a comprehensive structure for assessing the level of health, quality of life needs, designing, implementing, and evaluating public health programs. The design of this study is descriptive analytic survey approach and sampling is done by accidental sampling, in elderly families in Posbindu Work Area Bareng Health Center District Klojen Malang. Aim: The purpose of this study is to analyze the management of aging process problems. Result: Research result ; 46% of the elderly are aged between 66-70 years, 85% of the elderly live with children, 80% of the elderly have no leisure activities; all respondents have health insurance, 80% of respondents seek help for health facilities when sick, all respondents take care of the elderly independently, 71% of respondents conduct routine checks (Check Up) for their health 46% of respondents experience obstacles in health financing, 83% of respondents use Bicycles for health services, 86% of routine health workers provide counseling. Conclusion: There is good potential for the elderly to get more optimal care because there is plenty of free time and living with family. Family capacity is very likely to be developed because financially and in adequate means and distance from health facilities is very affordable.